The SCRIT electron scattering facility project at RIKEN RI beam factory. (26th November 2015) - Ohnishi, T; Enokizono, A; Hara, M; Hori, T; Ichikawa, S; Kurita, K; Matsuo, S; Suda, T; Tamae, T; Togasaki, M; Tsukada, K; Tsuru, T; et al.
Abstract: The self-confining RI target (SCRIT) electron scattering facility has been constructed at RIKEN RI Beam Factory. The commissioning experiment was performed, and the luminosity was achieved to around 10 27 cm −2 s −1 with stable ions at a 250 mA electron beam current. For the electron scattering with short-lived unstable nuclei, the radioactive isotope production was started at electron-beam-driven RI separator for SCRIT. Furthermore, new devices, the electron spectrometer window frame spectrometer for electron scattering and the cooler buncher system were constructed. After the setup of new devices, a first electron scattering experiment with short-lived nuclei will be performed soon.